Studi Fenomenologi: Faktor-Faktor yang Mempengaruhi Kegigihan Penyandang Tunanetra dalam Menguasai Alat Musik - Amiroh, Umaimatul; Kawuryan, Fajar (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to describe the factors influencing the perseverance of individuals with visual impairments in mastering musical instruments. Using a qualitative phenomenological approach, data were collected through in-depth interviews and observations involving three purposively selected participants with visual impairments. The findings show that perseverance is shaped by the interaction between internal factors interest, consistent practice, meaningful goals, and sustained hope, and external factors such as family support, teacher guidance, and an inclusive school environment. The novelty of this study lies in its focus on how these internal and external factors jointly construct perseverance in the context of music learning among individuals with visual impairments, a topic that remains limited in prior research. Although the sample size is small, the study provides practical implications for inclusive music education, particularly the need for adaptive teaching methods, tactile or audio-based learning materials, and continuous family-school collaboration to strengthen perseverance and musical skill development among visually impaired learners.